A new contact mat wireless system for estimating vertical jump height - Annino, G.; Federici, L.; Gabrieli, M.; Ranavolo, A.; Silvaggi, N.; Bonaiuto, V. (Procedia Engineering, 2016)
Among the different devices available for the assessment of the vertical jump height based on the flight time measurement, the contact mats are surely one of the simplest and portable systems and, for this reason, they are more widely used. This paper deals with the comparative evaluation of the performances of a new contact mat system with respect to a force platform. Some tests have been performed and the relative comparative results will be presented. The study shows a significant concurrent validity of Wi-JumpLe system for the flight and ground contact time measurements. In conclusion, the new contact mat structure together with the electronic measurement system is legitimate to assess vertical jump height and leg extensors muscle power.